Activation of liver alcohol dehydrogenase by glycosylation. - Tsai, C S (1983)
D-Fructose and D-glucose activate alcohol dehydrogenase from horse liver to oxidize ethanol. One mol of D-[U-14C]fructose or D-[U-14C]glucose is covalently incorporated per mol of the maximally activated enzyme. Amino acid and N-terminal analyses of the 14C-labelled glycopeptide isolated from a proteolytic digest of the [14C]glycosylated enzyme implicate lysine-315 as the site of the glycosylation. 13C-n.m.r.-spectroscopic studies indicate that D-[13C]glucose is covalently linked in N-glucosidic and Amadori-rearranged structures in the [13C]glucosylated alcohol dehydrogenase. Experimental results are consistent with the formation of the N-glycosylic linkage between glycose and lysine-315 of liver alcohol dehydrogenase in the initial step that results in an enhanced catalytic efficiency to oxidize ethanol.